An atomically-thin graphene reverse electrodialysis system for efficient energy harvesting from salinity gradient. (March 2019) - Fu, Yanjun; Guo, Xun; Wang, Yihan; Wang, Xinwei; Xue, Jianming
Abstract: Salinity gradient energy is a kind of the Gibbs free energy of mixing, and it is a clean, sustainable, and renewable energy source which is projected of the capacity to generate about 2.6 TW of electricity from all rivers flowing into the sea. However, the current technology to convert the salinity gradient energy to electricity suffers from low conversion efficiency, which results in a low output power density. In this work, we develop a new type of the graphene reverse electrodialysis (GRED) device which can efficiently convert the salinity gradient energy into electricity. The GRED device is fabricated based on a simple and straightforward ion irradiation perforation approach, and it is demonstrated to exhibit a record-high energy conversion efficiency of 39% and a record-high output power density of 27 W/m 2 at room temperature, manifesting its high promise for the clean energy harvesting from the salinity gradient. Theoretical simulations based on molecular dynamics and continuum theory further show that the charge at the pore edge is of crucial importance for achieving high ion selectivity. In light of this finding, we show that the output power density of GRED can be further boosted to 126 W/m 2 if it is operated at a slightly elevated temperature of 47 °C, for which the heating could be from industrial thermal waste in a practical sense. Graphical abstract: A new-type graphene reverse electrodialysis (GRED) device is fabricated to convert the salinity gradient energy into electricity, and the GRED device shows a high output power density up to 126 W/m 2 and a high energy conversion efficiency of 39%. fx1 Highlights: A new graphene reverse electrodialysis (GRED) device is fabricated. The GRED device can convert salinity gradient energy into electricity. The energy conversion efficiency of GRED can be up to 39%. The output power density can be 126 W/m 2 if it is operated at 47 °C. The ion selectivity of GRED is investigated by MD and PNP simulations.